2018
DOI: 10.1016/j.ijscr.2017.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Chondrometaplasia of the vocal cord in an adult male

Abstract: HighlightsA 62 year old man without any history of trauma presented with progressive dysphonia, dyspnoea, without any dysphagia.A fibreoptic laryngoscopic examination revealed nodular mass arising at the junction of posterior 1/3rd and middle 1/3rd of left vocal cord it was extending up to arytenoids.A computed tomography scan of the neck region showed a rounded and circumscribed mass without infiltration of the surrounding tissues. Histological investigation of the lesion revealed the presence of fibroelastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…1,2 However, there have been only a few previous case reports describing symptomatic laryngeal lesions consistent with chondroid metaplasia. [3][4][5][6] The etiology of chondroid metaplasia in the larynx is unclear, and a history of laryngeal trauma and laryngitis have been suggested as contributing factors to the development of metaplasia. 2 Nearly 80% of symptomatic patients with chondroid metaplasia reported a history of prior endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 However, there have been only a few previous case reports describing symptomatic laryngeal lesions consistent with chondroid metaplasia. [3][4][5][6] The etiology of chondroid metaplasia in the larynx is unclear, and a history of laryngeal trauma and laryngitis have been suggested as contributing factors to the development of metaplasia. 2 Nearly 80% of symptomatic patients with chondroid metaplasia reported a history of prior endotracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
“…Early histopathologic studies have demonstrated that microscopic foci of metaplastic cartilage are found in 1% to 2% of all examined larynges in human cadavers and incidentally in up to 9% of vocal fold surgical specimens . However, there have been only a few previous case reports describing symptomatic laryngeal lesions consistent with chondroid metaplasia . The etiology of chondroid metaplasia in the larynx is unclear, and a history of laryngeal trauma and laryngitis have been suggested as contributing factors to the development of metaplasia .…”
Section: Discussionmentioning
confidence: 99%
“…There are only few reports on chondrometaplasia of the larynx at present. Recently, Abdulmohsen Kamel AlBader [23] reported a case of chondrometaplasia of the vocal cords in a 62-year old man without trauma history. Early in 1981, Lyer…”
Section: Chondrometaplasia Of the Glottis In One Dog In Groupmentioning
confidence: 99%
“…The individual nuclei are small, single, homogenously dark, and lack mitotic activity. The key histological feature of chondrometaplasia, however, relates not to the individual cells which form the lesion but rather to the elastic cartilage matrix in which they are embedded [3].…”
Section: Chondrometaplasiamentioning
confidence: 99%
“…Chondrometaplasia is, in general, a lesion of adulthood; however, although it has not been reported in patients during the first decade of life, it has been described in patients ranging in age from the second decade of life to the tenth, with an average age at presentation of around 52 years [2, 47]. In the majority of cases, chondrometaplasia arises in the vocal cords and less often in the epiglottic region [3, 7, 8].…”
Section: Chondrometaplasiamentioning
confidence: 99%